10 watt-level tunable narrow linewidth 1.5 [STIX]x03BCm all-fiber amplifier. (6th June 2018) - Tang, Ni; Zhou, Zhiyue; Li, Zhixian; Wang, Zefeng
Abstract : We report here a high-power, wavelength tunable and narrow linewidth 1.5 [STIX]x03BCm all-fiber laser amplifier based on a tunable diode laser and Er-Yb co-doped fibers. The laser wavelength can be precisely tuned from 1535 nm to 1580 nm, which covers many absorption lines of mid-infrared laser gases, such as C_2H_2, HCN, CO, and HI. The maximum laser power is > 11 W, and the linewidth is about 200–300 MHz, which is close to the absorption linewidth of the above-mentioned gases. This work provides a suitable pump source for high-power wavelength tunable mid-infrared fiber gas lasers based on low-loss hollow-core fibers.